Endometriosis Patients in the Postmenopausal Period: Pre- and Postmenopausal Factors Influencing Postmenopausal Health. (1st June 2014) - Haas, Dietmar; Wurm, Peter; Schimetta, Wolfgang; Schabetsberger, Kathrin; Shamiyeh, Andreas; Oppelt, Peter; Binder, Helge
Abstract : Objective . To evaluate patients' health status and the course of endometriosis from the premenopausal to the postmenopausal period and evaluate influencing factors that may be relevant. Methods . Questionnaire completed by 35 postmenopausal women in whom endometriosis had been histologically confirmed premenopausally. Correlation and regression analyses were carried out to identify factors relevant to their postmenopausal health status. Results . Overall, there was clear improvement in typical endometriosis symptoms and sexual life. Clear associations (P < 0.005 ) were observed between premenopausal factors like physical limitations caused by the disease, impaired social contacts and psychological problems, and postmenopausal pain and impairment of sexual life. Three statistical models for assessing pain and impairment of sexual life in the postmenopausal period were calculated on the basis of clinical symptoms in the premenopausal period, with a very high degree of accuracy (P < 0.001 ; R 2 = 0.833/0.857/0.931). Conclusions . The results of the survey strongly suggest that physical fitness and freedom from physical restrictions, a good social environment, and psychological care in both the premenopausal and postmenopausal periods lead to marked improvements in the postmenopausal period with regard to pain, dyspareunia, and influence on sexual life in endometriosis patients.